2010
DOI: 10.1002/etc.307
|View full text |Cite
|
Sign up to set email alerts
|

Stability, preservation, and quantification of hormones and estrogenic and androgenic activities in surface water runoff

Abstract: Degradation of hormones that may occur during storage of surface water samples can lead to underestimations in estrogenic and androgenic activities and inaccuracies in hormone concentrations. The current study investigated the use of sodium azide, hydrochloric acid (HCl), and sulfuric acid (H₂SO₄) to inhibit the degradation of hormones and estrogenic and androgenic activities in samples of surface water runoff from cattle manure-amended fields during storage at 4°C. Hormones and hormone metabolites were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…4). In addition, during a prolonged rain event, P4 could continuously be washed into aquatic environments from concentrated animal feeding operations at concentrations as high as 375 ng/L [7]. 4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4). In addition, during a prolonged rain event, P4 could continuously be washed into aquatic environments from concentrated animal feeding operations at concentrations as high as 375 ng/L [7]. 4).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the potential for chronic exposure, it has been reported that sustained levels of P4 can enter aquatic environments from wastewater treatment plants with concentrations in the range of 5 to 199 ng/L [8]. In addition, during a prolonged rain event, P4 could continuously be washed into aquatic environments from concentrated animal feeding operations at concentrations as high as 375 ng/L [7]. Given these high levels and the ubiquitous presence of P4 in the environment and its effects on fish reproduction, we conclude that P4 is a significant EDC that warrants more attention from investigators and managers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pH of water samples was adjusted to about 3 by adding hydrochloric acid so as to fix the estrogens. The added acid suppressed microbial activity which could degrade the estrogens to some extent before analysis (Havens et al, 2010). Thereafter, the samples were carried in cool box packed with ice packs to the Ecotoxicology and Natural Products research Laboratory in the Faculty of Veterinary Medicine at Sokoine University of Agriculture, for pretreatment and solid phase extraction of estrogens that was done within 12 h after sample collection.…”
Section: Sampling Of Water Samplesmentioning
confidence: 99%